1999
DOI: 10.1136/thx.54.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Specific IgG subclass antibody pattern to Aspergillus fumigatus in patients with cystic fibrosis with allergic bronchopulmonary aspergillosis (ABPA)

Abstract: Background-IgG and IgG subclass antibodies to Aspergillus fumigatus (A fumigatus) were measured in a large population of patients with cystic fibrosis to elucidate a putative antibody pattern specific for allergic bronchopulmonary aspergillosis (ABPA). Conclusions-In a large number of unselected patients with cystic fibrosis significantly increased levels of Af-specific antibodies belonging to total IgG and all four subclasses were found in all groups of patients compared with healthy controls. In patients per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…Anti-Aspergillus IgG levels are directly related to carriage of the microbe, while anti-Aspergillus IgA levels are inversely related to carriage (270). A positive correlation between fungal carriage and antifungal IgG antibodies is supported by a more recent study (299). These data seem to support a prominent role of IgA in protection in normal individuals, and they indicate that in CF patients, some host defense factor is compromised that dysregulates the humoral response, causing the production of unprotective antibodies.…”
Section: Emerging Pathogens Affecting Cystic Fibrosis Patientsmentioning
confidence: 76%
“…Anti-Aspergillus IgG levels are directly related to carriage of the microbe, while anti-Aspergillus IgA levels are inversely related to carriage (270). A positive correlation between fungal carriage and antifungal IgG antibodies is supported by a more recent study (299). These data seem to support a prominent role of IgA in protection in normal individuals, and they indicate that in CF patients, some host defense factor is compromised that dysregulates the humoral response, causing the production of unprotective antibodies.…”
Section: Emerging Pathogens Affecting Cystic Fibrosis Patientsmentioning
confidence: 76%
“…81 Although previous works detected no association between ABPA and P. aeruginosa colonisation. 82 Nikolaizik et al reported a positive correlation between the two entities, suggesting that P. aeruginosa colonisation favours the process of A. fumigatus sensitisation. 83 The causal relationship between Aspergillus sensitisation and Pseudomonas colonisation has motivated great discussion over the years as it is difficult to disentangle the influences of the Pseudomonas from that of Aspergillus.…”
Section: Abpamentioning
confidence: 99%
“…After withdrawal of itraconazole treatment, all the patients were closely controlled with specific IgG subclass antibodies to A. fumigatus [24] in order to follow the activity of ABPA. In patients with increasing specific IgG subclass antibodies and clinical signs of exacerbation in ABPA, itraconazole treatment was restarted after withdrawal of budesonide.…”
Section: Follow-upmentioning
confidence: 99%